INDEX NUMBERS LASPEYRES FIND CAR SALES IN PT. ASTRA INTERNATIONAL TBK TOYOTA KEBON JERUK APPLICATIONS USING TURBO PASCAL VERSION 7.0 - Jepri Sinaga; Aqwam Rosadi Kardian, SKom., MM. (Jurnal Sistem Informasi, 2006)
Laspeyres index numbers is a popular statistical tools to measure the change orperform a comparison between the variables in a few years for comparison. Discussedin this writing about how the formula for rate applied Laspeyres index into Pascalprogramming, both implemented into the Laspeyres index formula and the dataavailable and discussing the problem with using the algorithm and to Flowchart isthen performed using the program making the programming language Turbo Pascal7.0.